Pengembangan Video Pembelajaran Tata Rias Wajah Geriatri dengan Ilusi Face Lift - Aisyah Sajida; Sitti Nursetiawati; Aniesa Puspa Arum (Journal on Education, 2024)
This research appears from the condition of students of the Cosmetology Education Study Program who have several difficulties in understanding geriatric facial makeup learning through available learning media. The researcher then developed a product in the form of a learning video of Geriatric Facial Makeup with the Illusion of FaceLift with the aim of producing feasible and practical learning media to be used as a learning resource and additional reference so as to strengthen students' knowledge in learning geriatric facial makeup in the Facial Makeup Course. Media in the form of learning videos can also be accessed independently without space and time limitations. The research is prepared using the Research and Development method and developed using the 4-D development model approach which consists of 4 (four) stages, namely Define, Design, Development, and Disseminate. The development stage has gone through a validation test stage carried out by material experts through three stages and a feasibility score of 96.6% was obtained. Furthermore, the validation test conducted by media experts went through two stages with a feasibility score of 98.2%. A practicality test was also carried out with a score of 89.3% at the individual trial stage and 92.9% at the practicality test stage with a limited trial. Based on the acquisition of these scores, the product of this research, namely the Geriatric Facial Makeup learning video with the illusion of FaceLift, was declared "Very Feasible" and "Very Practical" and can be used as a learning medium for geriatric facial makeup.